2008
DOI: 10.1088/0953-8984/20/04/045217
|View full text |Cite
|
Sign up to set email alerts
|

Defect studies in annealed ZnO by positron annihilation spectroscopy

Abstract: Coincidence Doppler broadening of the positron annihilation technique has been employed to identify the defects in thermally annealed 'as-received' ZnO and thermally annealed ball-milled nanocrystalline ZnO. Results indicate that a significant amount of oxygen vacancy has been created in ZnO due to annealing at about 500 • C and above. The results also indicate that the Zn vacancy created during the ball milling process can be easily removed by annealing the sample at about 500 • C and above. The defect charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…An experimental study corresponding to those findings has been performed by Sanyal et al [57]. The group was ball-milling ZnO powder and subsequently annealing it in air up to 873 K. Applying positron annihilation spectroscopy (PAS), they found mainly Zn vacancies inside the as-milled powders.…”
Section: Role Of the Defects 41 Intrinsic Defects In Znomentioning
confidence: 86%
See 1 more Smart Citation
“…An experimental study corresponding to those findings has been performed by Sanyal et al [57]. The group was ball-milling ZnO powder and subsequently annealing it in air up to 873 K. Applying positron annihilation spectroscopy (PAS), they found mainly Zn vacancies inside the as-milled powders.…”
Section: Role Of the Defects 41 Intrinsic Defects In Znomentioning
confidence: 86%
“…The parameters investigated are the isomer shift, the quadrupole and the magnetic hyperfine splitting at the nucleus. Early investigations on solid solutions of 57 Fe, Zn and O mainly revealed oxide spinel secondary phases to be responsible for magnetic sextets observed [42,43]. There are other methods basing on radioactive probes which definitely have the potential to give more insight into the origin of ferromagnetic properties in TM doped ZnO.…”
Section: Analysis Techniques Inmentioning
confidence: 99%
“…The presence of oxygen vacancies expands the ZnO lattice [18]. It has been reported [19,20] that a significant amount of oxygen vacancy has been created and interstitial zinc atoms have been obtained enough energy and reverted to the crystal lattice site (recombined with Zn vacancies) by annealing the polycrystalline ZnO in air at about 500 °C. Furthermore, it has been reported that the interstitial zinc atoms have been reverted to the crystal lattice site in the ZnO:Co films when annealed in air at 600 °C [21].…”
Section: Methodsmentioning
confidence: 99%
“…Annealing of crystals is one possible way of recovering defects or removing them. The study of defects in ZnO through annealing has been performed using the Hall effect, 9-11 positron annihilation spectroscopy, 12 x ray diffraction, Rutherford backscattering spectroscopy (RBS), admittance spectroscopy, 13 cathodoluminescence, and photoluminescence. 14 In this paper, we study the effects of annealing on ZnO and the electrical properties of the devices formed on the annealed material.…”
Section: Introductionmentioning
confidence: 99%